A Framework for Explaining Teachers' Diagnostic Judgements by Cognitive Modeling (DiaCoM). (May 2020) - Loibl, Katharina; Leuders, Timo; Dörfler, Tobias
Abstract: Research on diagnostic competencies of teachers nowadays raises the question which person or situational characteristics moderate judgement accuracy. Beside this correlational approach, a stronger interest in understanding the cognitive processes involved in the genesis of diagnostic judgements has emerged. To address the theoretical gap regarding cognitive processes underlying diagnostic judgements, we propose a framework, called DiaCoM (Explaining Teachers' Diagnostic Judgements by Cognitive Modeling). It aims at supporting (existing or envisioned) research that strives to test cognitively oriented explanations for processes and products of diagnostic judgements of teachers. Graphical abstract: Image 1 Highlights: The DiaCoM framework models diagnostic judgements as information processing. It systematizes the role of teacher and situation characteristics in diagnostic thinking. The DiaCoM framework allows deriving and testing cognitive oriented hypotheses. It supports coherent interpretation across studies and inspires further research.